Adding access blood flow surveillance reduces thrombosis and improves arteriovenous fistula patency: a randomized controlled trial. Issue 4 (July 2017) - Aragoncillo, Inés; Abad, Soraya; Caldés, Silvia; Amézquita, Yésika; Vega, Almudena; Cirugeda, Antonio; Moratilla, Cristina; Ibeas, José; Roca-Tey, Ramón; Fernández, Cristina; Macías, Nicolás; Quiroga, Borja; et al.
Purpose: Stenosis is the main cause of arteriovenous fistula (AVF) failure. It is still unclear whether surveillance based on vascular access blood flow (QA ) enhances AVF function and longevity. Methods: We conducted a three-year follow-up randomized, controlled, multicenter, open-label trial to compare QA -based surveillance and pre-emptive repair of subclinical stenosis with standard monitoring/surveillance techniques in prevalent mature AVFs. AVFs were randomized to either the control group (surveillance based on classic alarm criteria; n = 104) or to the QA group (QA measured quarterly using Doppler ultrasound [ M-Turbo ® ] and ultrasound dilution [Transonic ® ] added to classic surveillance; n = 103). The criteria for intervention in the QA group were: 25% reduction in QA, QA <500 mL/min or significant stenosis with hemodynamic repercussion (peak systolic velocity [PSV] more than 400 cm/sc or PSV pre-stenosis/stenosis higher than 3). Results: At the end of follow-up we observed a significant reduction in the thrombosis rate in the QA group (0.025 thrombosis/patient/year in the QA group vs. 0.086 thrombosis/patient/year in the control group [p = 0.007]). There was a significant improvement in the thrombosis-free patency rate (HR, 0.30; 95% CI, 0.11-0.82; p = 0.011) and in the secondary patency rate in the QA group (HR, 0.49; 95% CI, 0.26-0.93; p = 0.030), with no differences in the primary patency rate between the groups (HR, 0.98; 95% CI, 0.57-1.61; p = 0.935). There was greater need for a central venous catheter and more hospitalizations associated with vascular access in the control group (p = 0.034/p = 0.029). Total vascular access-related costs were higher in the control group (€227.194 vs. €133.807; p = 0.029). Conclusions: QA -based surveillance combining Doppler ultrasound and ultrasound dilution reduces the frequency of thrombosis, is cost effective, and improves thrombosis free and secondary patency in autologous AVF.